Initial provisions of state regulation of regional human development - Stolyarov, V.; Shynkaryuk, O.; Stolyarova, V. (Економічний вісник Донбасу, 2018)
The article reveals the leading elements of the state regulation of regional human development. The logical scheme of formation of the mechanism and algorithm of its functioning is given.
The necessity of assessing the effectiveness and efficiency of the mechanism of state regulation of regional human development based on the results of the evaluation of the components and in general of the Regional Human Development Index is emphasized. У статті розкрито вихідні положення державного регулювання регіонального людського розвитку. Наведено логічну схему формування механізму та алгоритм його функціонування.
Наголошено на необхідності оцінки результативності і ефективності механізму державного регулювання регіонального людського розвитку за результатами оцінки складових та в цілому Індексу регіонального людського розвитку. В статье раскрыты исходные положения государственного регулирования регионального человеческого развития. Представлены логическая схема формирования механизма и алгоритм его функционирования.
Акцентировано на необходимости оценки результативности и эффективности механизма государственного регулирования регионального человеческого развития по результатам оценки составляющих и в целом Индекса регионального человеческого развития.